FARMERS’ PERCEPTION ON THE EFFECTS OF CLIMATE CHANGE ON YAM PRODUCTION IN PLATEAU STATE, NIGERIA - Silas Y.G.; Bose A.A.; Garba, M.; Atman F.M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined farmers’ perception on the effects of climate change on yam production among farmers in Plateau State, Nigeria. The objectives of the study had specific objectives as were to describe the socio-economic characteristics of yam farmers in the study area ; determine yam farmer’s perception of the effects of climate change; identify yam farmers’ sources of information on the effects of climate change and describe the constraints to yam farmers in the adaptation strategies of climate change to of climate mitigation strategies of the effects of climate change in the study area Multi-stage sampling techniques were employed in selecting 321 respondents. Data were collected through the administration of structured questionnaire and analyzed using descriptive statistics. . The findings revealed that the majority of the respondents were male 70.9% and married (71.2%), with a mean age and household size of 43 years and 10 persons, respectively. Majority (58.6%) had formal education(primary, secondary or tertiary). The mean farming experience (14 years while farm size was 6.35ha). The finding also revealed that respondents perceived climate change having serious adverse effects on yam production as indicated by mean scores in reduction in soil fertility(Mean=3.1), shortage of water,(Mean =3.1) poor germination(Mean=3) and incessant flooding with a mean score of 3.1, 3.1, 3.0 and (Mean =3.0) respectively. The results also revealed that Majority (55.4%) of the respondents reported that the nature of climate change effects moderately reduced yam yield moderately reduced yam yield while 25.3% reported that it reduced yield. The findings further revealed that farmers relied heavily on personal experience ranked 1st(96.8%), markets (94.9%), fellow farmers (92.7%), and village/market meetings (89.2%) to source of information on climate change.. The major constraints to adaptation of climate change mitigation strategies included inefficiency of information sources (Mean = 2.8), high cost of irrigation facilities (Mean = 2.8), and inadequate government support (Mean = 2.7).The study concluded that farmers in the study area clearly perceived climate change as a serious threat to yam production. Sources of information on climate change were mainly through the of personal sources of information. Therefore, improving institutional support systems and reducing structural barriers are critical to strengthening climate resilience among yam farmers. It is recommended that yam farmers’ socio-economic status should be enhanced to enable them afford and adopt proven technologies that would mitigate climate change and Extension agents who are supposed to be in close contact with the yam farmers should be trained on weather forecasts interpretation so as to disseminate the same needed information to their contact farmers on Adaptive strategies, such as Climate Smart Agriculture and climate-resilient crop varieties should be encouraged for adoption.